2017
DOI: 10.1556/0806.44.2016.054
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of maize cultivars adapted to tropical environments using AMMI analysis

Abstract: Genotype × environment interactions complicate selection of superior genotypes for narrow and wide adaptation. Eighteen tropically-adapted maize cultivars were evaluated at six locations in Nigeria for 2 yrs to (i) identify superior and stable cultivars across environments and (ii) assess relationships among test environments. Environment and genotype × environment interactions (GEI) were significant (P < 0·05) for grain yield. Environments accounted for 63.5% of the total variation in the sum of squares for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
4
21
0
Order By: Relevance
“…These results highlight the necessity of multi-year and multi-location testing, before hybrid could be recommended for a certain region. This is in accordance with OYEKUNLE et al (2017b).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results highlight the necessity of multi-year and multi-location testing, before hybrid could be recommended for a certain region. This is in accordance with OYEKUNLE et al (2017b).…”
Section: Resultssupporting
confidence: 92%
“…AMMI model found its application in testing of interactions genotype x environment (GxE), genotype x year (GxY), or genotype x environment x year (GxExY) in different crops: sugar beet (ĆIRIĆ et al, 2017), onion (PAVLOVIĆ et al, 2017, spring barley (PRŢULJ et al, 2015), barley (MIROSAVLJEVIĆ et al, 2014, triticale (KAYA and OZER, 2014), soybean (SOUSA et al, 2015), perennial ryegrass (LAKIĆ et al, 2015), rice (BOSE KUMAR et al, 2014), and of course maize (MITROVIĆ et al, 2012;NZUVE et al, 2013;SHIRI 2013;KRIŢMANIĆ et al, 2014;ОYEKUNLE et al, 2017a;2017b;BADU-APRAKU et al, 2011).…”
mentioning
confidence: 99%
“…For the early and medium groups, this approach provided three of the more stable clusters and for the late-maturity genotypes, four stable environmental strata were produced (Table 4). These results agree with those obtained by other authors, in environmental stratification studies for sorghum grain yield (Rakshit et al, 2012), barley (Mohammadi et al, 2009;Mortazavian et al, 2014), and maize (Oyekunle et al, 2017). The AMMI1 model offers greater repeatability of the clusters, concerning more parameterized AMMI models, which incorporate more axes of the GxE interaction (Gauch, 1990(Gauch, , 1992Ebdon and Gauch, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Studies with a relatively low percentage of explanation in IPCA1 were observed in trials with Brassica spp. (38.6–54.6% [Bocianowski et al, 2019]); sugarcane (32.9‐35% [Ramburan et al, 2011]); maize (26.4% [Balestre et al, 2009)] and 40.8% [Oyekunle et al, 2017]); and wheat (43.5% [Bornhofen et al, 2017]; 32.1% [Tigabu et al, 2017]; 33.1‐38.2% [Veenstra et al, 2019]). In this sense, biplots with low GEI pattern recovery must be interpreted cautiously in trial networks with prevalence of crossover interaction, since only the simple part of the GEI can be represented in the first main components and the complex part of the GEI may be discarded.…”
Section: Discussionmentioning
confidence: 99%